On the Error Rate Analysis of Dual-Hop Amplify-and-Forward Relaying in Generalized-K Fading Channels - George P. Efthymoglou; Nikolaos Bissias; Valentine A. Aalo (Journal of Electrical and Computer Engineering)
We present novel and easy-to-evaluate expressions for the error rate performance of cooperative dual-hop relaying with maximal ratio combining operating over independent generalized-𝐾 fading channels. For this system, it is hard to obtain a closed-form expression for the moment generating function (MGF) of the end-to-end signal-to-noise ratio (SNR) at the destination, even for the case of a single dual-hop relay link. Therefore, we employ two different upper bound approximations for the output SNR, of which one is based on the minimum SNR of the two hops for each dual-hop relay link and the other is based on the geometric mean of the SNRs of the two hops. Lower bounds for the symbol and bit error rates for a variety of digital modulations can then be evaluated using the MGF-based approach. The final expressions are useful in the performance evaluation of amplify-and-forward relaying in a generalized composite radio environment.